Non-Invasive Assessment of Peripheral Arterial Disease (PAD) in Lower Limbs in Patients with Established Coronary Artery Disease - Hai, Abdul; Fazal Ur Rehman,; Ahmed, Adil; Khan, Ajab; Rehmatullah,; Ali, Abdul (Indus Journal of Bioscience Research, 2025)
Background: Peripheral arterial disease (PAD) is prevalent in coronary artery disease (CAD) patients, reflecting systemic atherosclerosis. Early detection via ankle-brachial index (ABI) and Doppler ultrasound aids risk stratification and management. This study assesses PAD prevalence, severity, and its correlation with cardiovascular risk factors. Study design: A cross-sectional study. Place and duration of study. From August 2024 to January 2025 Cardiology Department Bolan Medical Complex Hospital Quetta/ Sandeman Provincial Hospital, Quetta. Methods: This cross-sectional study included 200 patients with established CAD. Patients underwent a comprehensive non-invasive vascular assessment, including ankle-brachial index (ABI) measurement and Doppler ultrasound for arterial flow analysis. PAD was diagnosed based on an ABI ≤ 0.90. Demographic, clinical, and laboratory data were recorded. The mean age, standard deviation (SD), and statistical significance (p-value) of PAD prevalence in CAD patients were calculated using appropriate statistical tests. A p-value < 0.05 was considered statistically significant. Results: A total of 200 CAD patients were evaluated, with a mean age of 64.5 ± 9.2 years. Among them, 45% (90 patients) had PAD, diagnosed using an ABI ≤ 0.90. The prevalence of PAD was significantly higher in diabetic patients (p < 0.01) and those with hypertension (p = 0.03). The mean ABI value in the PAD group was 0.78 ± 0.10, compared to 1.02 ± 0.12 in the non-PAD group (p < 0.001). Doppler ultrasound revealed significant arterial stenosis in 30% of PAD patients. Patients with PAD had a higher incidence of claudication and reduced exercise tolerance. Statistical analysis confirmed a strong correlation between PAD severity and traditional cardiovascular risk factors. Conclusion: This study reports a 45% prevalence of PAD in CAD patients, highlighting its association with diabetes and hypertension. Early detection using ABI and Doppler ultrasound can improve risk stratification, management, and patient outcomes.